Reputation for technological innovation: Does it actually cohere with innovative activity? - Patrick J. Höflinger; Christian Siegfried Anton Nagel; Philipp Sandner (Journal of Innovation & Knowledge (JIK), 2018)
Firms strategically promote, foster and pursue a reputation for technological innovation. Yet, present research did not examine whether such perception actually coheres with innovative activity itself. Previous studies in this field often relied solely on tangible products/product introductions, hence we apply multiple proxies based on a firm's intangible innovative performance to examine the influences on reputation for technological innovation. Using patent, financial and consumer data our Poisson regression analyzes 65 international firms which have been nominated by 231 consumers. We apply time-series and likewise cross-sectional data for our interdisciplinary analysis. Our findings demonstrate that innovative performance (citation intensity) is linked to reputation for technological innovation. Counter-intuitively, our results provide evidence that marketing intensity negatively influences a reputation for technological innovation. From the results, we conclude that innovative performance may be associated with a reputation for technological innovation. Actual technological advancement attracts attention from consumers that cannot be purchased with greater marketing investments. This implies that consumers appreciate the costly and uncertain R&D efforts and value those firms that constantly offer innovation. As a theoretical implication, the consideration of intangible inputs for reputation research is an important contribution for a holistic understanding. The results represent essential strategic information for innovation and marketing functions, where both divisions need to align their activities and investments.
Keywords: M01; M31; O30; O31; O32; 650; Technological innovation; Innovative performance; Reputation; Patents